Field description in work integration: part 1 of deliverable 7.1. of the project: "Impact of the third sector as social innovation" (ITSSOIN), European Comission - 7th Framework Programme - Lallemand-Stempak, Nathalie; Cognat, Aurelie; André, Kévin; Pache, Anne-Claire; Preuß, Stina; Navrátil, Jiří; Špalková, Dagmar; Rey-Garcia, Marta; Calvo, Nuria; Felgueiras, Ana (European Commission, DG Research, 2015)
Deliverable of the FP-7 project: ITSSOIN (613177) Suggested citation Lallemand-Stempak, A.; Cognat, S.; André, K.; Pache, A-C.; Preuss, S.; Navrátil, J.; Špalková, D.; Rey-García, M.; Calvo Babio, N.; Felgueiras A. (2015).
Deliverable of the FP-7 project: ITSSOIN (613177)
Gesehen am 19.06.2023